When multiple identities compete: The role of centrality in self‐brand connections. Issue 6 (7th November 2013) - Harmon‐Kizer, Tracy R.; Kumar, Anand; Ortinau, David; Stock, James
ABSTRACT The current research provides a framework for understanding how centrality impacts people's choice of brands and related brand connectedness. Motivated by the need to validate their self‐image, individuals use brands to express and confirm their identities. The authors hypothesize that greater centrality of the identity to the self strengthens the connectedness an individual has for brands with value‐expressive properties. Three studies using experimental designs examined whether people whose identity is central to their self‐conception leads to stronger self‐brand connectedness than peripheral identities. In study 1, the results showed that people whose shopping identity was central (versus peripheral) to their self‐concept led to stronger self‐brand connections. Study 2 replicated the findings of study 1 employing brand symbolism as a moderator. Brands high in symbolic properties led to stronger brand connections for an individual's central identities compared with their peripheral identities. Study 3 replicated the influence of centrality on brand choice and self‐brand connections by generalizing this effect to reference group identities. Collectively, the studies provide evidence that individuals integrate brand associations into their self‐concept on the basis of both the centrality of the identity and the level of symbolism the brands holds for an identity. Copyright © 2013 John Wiley & Sons, Ltd.